Synthesis and Utility of Dihydropyridine Boronic Esters. (22nd December 2015) - Panda, Santanu; Coffin, Aaron; Nguyen, Q. Nhu; Tantillo, Dean J.; Ready, Joseph M.
Abstract: When activated by an acylating agent, pyridine boronic esters react with organometallic reagents to form a dihydropyridine boronic ester. This intermediate allows access to a number of valuable substituted pyridine, dihydropyridine, and piperidine products.